Dampak Perubahan Iklim Terhadap Produksi, Kualitas Hasil Dan Pendapatan Petani Kopi Arabika Di Aceh Tengah - Heru P Widayat; Ashabul Anhar; Akhmad Baihaqi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. Arabica coffee grown in the Gayo Highlands, which includes Central Aceh, Bener Meriah and Gayo Lues district. The impact of climate change, affect the aspects related to the cultivation of coffee. The research objective is to determine the productivity, quality of results and arabica coffee farmers' income from various types kentianggian arabica coffee cultivation. The study was conducted in an area with a height difference of 1000-1200, 1200-1400, and 1400-1600 m above sea level. Coverage of further research is the analysis of the aspects that affect production, quality of results, and the income of farmers. Data collected by purposive sampling technique. Primary data were gathered through observation, interviews and focus group discussions.The results were obtained, Productivity arabica coffee ranged between 250-750 kg / ha / year. The regression analysis shows, production, altitude, farmers' income, the number of stems, soil conservation, crop care, harvesting patterns, treatment outcome, drying, storage, fruit production, pest and disease control and land a positive effect. Coffee quality of areas, production of the shade management, negative effect.